Comparative Analysis of Thermomechanical Properties and Thermal Damage Constitutive Models of Three Soft Sedimentary Rocks - Wenhua Zha; Weixing Shao; Suqin Yao; Qiang Chen; Denghong Chen (Advances in Civil Engineering)
In order to study the difference in thermomechanical properties of soft sedimentary rocks of different coal measures, three types of soft sedimentary rocks, sandstone, sandy mudstone, and mudstone, which are common in deep mines, are tested using the RMT-150B rock mechanics test system and GD-65/150. Uniaxial compression experiments were conducted on three kinds of soft rock-cement mixed specimens at 25°C～55°C multistage temperature in an environmental chamber. The difference of important parameters such as stress-strain curve, peak stress, and elastic modulus was analyzed and compared. The results show that (i) in the test temperature range, the stress-strain curves of the three types of soft rocks at different temperatures are roughly divided into four stages: compaction, elasticity, yield, and failure. The proportion of deformation in the compaction stage to the total deformation decreases gradually with the increase of temperature. (ii) When the temperature is lower than 40°C, the yield stage is shorter, and the peak stress and elastic modulus of the three types of soft rocks decrease significantly with the increase of temperature. (iii) Above 40°C, the decreasing trend of peak stress and elastic modulus curve decreases, and the yield stage becomes more and more obvious. The decreasing rate of elastic modulus of sandstone is 0.041 GPa/°C; the decreasing rate of peak stress is 0.193 MPa/°C, the decreasing rate of sandy mudstone is 0.022 GPa/°C and 0.124 MPa/°C, and the decreasing rate of mudstone is 0.020 GPa/°C and 0.051 MPa/°C. (iv) The rationality of the established thermal damage constitutive model of sedimentary soft rock was verified.